THE EIGHTH DAY ARGUMENT: A JEWISH RATIONALE FOR THE REJECTION OF THE SEVENTH DAY SABBATH - Alves Oliveira Neto, Maviael (Práxis Teológica, 2024)
.Building from the assumption of the Sabbath’s obsolescence much has been argued for the prominence of Sunday gatherings already in the New Testament corpus, or even that Jesus, though a Sabbath keeper, paved the way for the substitution of the seventh day Sabbath, which is by no means self-evident and therefore deserves further investigation. Ad interim, irrespective of the proper biblical interpretation of the continuity of the seventh day Sabbath, only voluntary blindness would deny the clear presence of the Sunday as a day to gather and worship within the Apostolic Fathers’ literature only a few decades after the last documents of the New Testament were written, at the pace that rejecting that which is Jewish was on vogue. Undoubtedly, the post apostolic treatment of the Sabbath is unprecedented given the Jewish origins of most New Testament writers, at the pace that the resurrection of Jesus became the main reason to account for the novelty of either worshiping on or keeping the Sunday. But how? What was the theological route that brought about such a phenomenon, i.e., that the Old Testament Sabbath became void on the basis of the resurrection of Jesus. Whereas Bacchiocchi, and many in his footsteps, find in the confluence of paganism, anti-Jewish sentiment and the prominence of the church in Rome as reasons that account for the suppression of the Sabbath in favour of the Sunday or Lord’s Day, there remains a need to explore the process through which such a belief came to be in the first place, hence the question: how did the resurrection of Jesus become the hermeneutical framework for the rejection of the Sabbath? It is on the elucidation of this question that the goal for this article is to be found.